ANALYSIS OF THE IMPACT OF THE DISCOVERY LEARNING MODEL ON STUDENTS' LEARNING ACTIVITIES AND CRITICAL THINKING SKILLS - Miftahus Surur; Zaki Emyus Ahmad Zaki Emyus; Yana Indah; Karunia Dewi Siti (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
This research aims to determine the effect of model Discovery learning on enhanced critical thinking ability and students' activation abilities. The methods used in this study are literature review methods to analyze the influence of advanced learning models. Data collection techniques using documentation, by searching journals that are relevant to this topic through Google Scholar with the last 5-year period from 2019-2023. Based on the result of 10 analyses of the article that it was obtained Information; 1) the application of the discovery learning model can provide a profound influence in improving and developing students’ critical thinking skills; 2) the application of the discovery learning model can provide a profound influence in improving students' learning activities. The conclusion of this study is that fact a discovery learning model can develop critical thinking ability and students' learning activities